Dodecenylsuccinic anhydride derivatives of gum karaya (Sterculia urens): preparation, characterization, and their antibacterial properties - Padil, Vinod Vellora Thekkae; Senan, Chandra; Černík, Miroslav (Journal of agricultural and food chemistry, 2015)
Esterifications of the tree-based gum, gum karaya (GK), using dodecenylsuccinic anhydride (DDSA) were carried out in aqueous solutions. GK was deacetylated using alkali treatment to obtain deacetylated gum karaya (DGK). The DGK and its DDSA derivative were characterized using gel permeation chromatography/multiangle laser light scattering (GPC/MALLS), attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), scanning electron microscopy (SEM), proton nuclear magnetic resonance spectroscopy ((1)H NMR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) analysis, and rheological studies. The degree of substitution was found to be 10.25% for DGK using (1)H NMR spectroscopy. The critical aggregation concentration of DDSA-DGK was determined using dye solubilization and surface tension methods. The antibacterial activity of the DDSA-DGK derivative was then investigated against Gram-negative Escherichia coli and Pseudomonas aeruginosa and Gram-positive Staphylococcus aureus. The DDSA-DGK derivative has the potential for use as a stabilizing agent in food and nonfood applications. It can also be developed as an antibacterial agent.
Keywords: Plant Extracts; rostlinné extrakty; antibacterial activity; deacetylated gum karaya; guma karaya; Succinic Anhydrides; thermal study; tree polysaccharides; rheological property; Karaya Gum; DDSA (dodecenylsuccinic anhydride) derivative; antibakteriální látky; anhydridy kyseliny jantarové; Anti-Bacterial Agents; Bacteria; Sterculia